On lions, impala, and bigraphs: modelling interactions in physical/virtual spaces - Benford, Steve; Calder, Muffy; Rodden, Tom; Sevegnani, Michele (Association for Computing Machinery, 2016)
While HCI has a long tradition of formally modelling task-based interactions with graphical user interfaces, there has been less progress in modelling emerging ubiquitous computing systems due in large part to their highly contextual nature and dependence on unreliable sensing systems. We present an exploration of modelling an example ubiquitous system, the Savannah game, using the mathematical formalism of bigraphs, which are based on a universal process algebra that encapsulates both dynamic and spatial behaviour of autonomous agents that interact and move among each other, or within each other. We establish a modelling approach based on four perspectives on ubiquitous systems—Computational, Physical, Human, and Technology—and explore how these interact with one another. We show how our model explains observed inconsistencies in user trials of Savannah, and then, how formal analysis reveals an incompleteness in design and guides extensions of the model and/or possible system re-design to resolve this.